Human Papillomavirus 16 E6 and E7 Synergistically Repress Innate Immune Gene Transcription - Claire D. James (American Society for Microbiology, 2020)
ABSTRACT Human papillomaviruses (HPV) are causative agents in 5% of all cancers, including the majority of anogenital and oropharyngeal cancers. Downregulation of innate immune genes (IIGs) by HPV to promote the viral life cycle is well documented; E6 and E7 are known repressors of these genes. More recently, we demonstrated that E2 could also repress IIGs. These studies have been carried out in cells overexpressing the viral proteins, and to further investigate the role of individual viral proteins in this repression, we introduced stop codons into E6 and/or E7 in the entire HPV16 genome and generated N/Tert-1 cells stably maintaining the HPV16 genomes. We demonstrate that E6 or E7 individually is not sufficient to repress IIG expression in the context of the entire HPV16 genome; both are required for a synergistic repression. The DNA damage response (DDR) is activated by HPV16 irrespective of E6 and E7 expression, presumably due to viral replication; E1 is a known activator of the DDR. In addition, replication stress was apparent in HPV16-positive cells lacking E6 and E7, manifested by attenuated cellular growth and activation of replication stress genes. These studies led us to the following model. Viral replication per se can activate the DDR following infection, and this activation is a known inducer of IIG expression, which may induce cellular senescence. To combat this, E6 and E7 synergistically combine to manipulate the DDR and actively repress innate immune gene expression promoting cellular growth; neither protein by itself is able to do this. IMPORTANCE The role of human papillomavirus 16 (HPV16) in human cancers is well established; however, to date there are no antiviral therapeutics that are available for combatting these cancers. To identify such targets, we must enhance the understanding of the viral life cycle. Innate immune genes (IIGs) are repressed by HPV16, and we have reported that this repression persists through to cancer. Reversal of this repression would boost the immune response to HPV16-positive tumors, an area that is becoming more important given the advances in immunotherapy. This report demonstrates that E6 and E7 synergistically repress IIG expression in the context of the entire HPV16 genome. Removal of either protein activates the expression of IIGs by HPV16. Therefore, gaining a precise understanding of how the viral oncogenes repress IIG expression represents an opportunity to reverse this repression and boost the immune response to HPV16 infections for therapeutic gain.